ROLE OF ICTS IN BRIDGING THE GENDER GAP OF INFORMATION REGARDING LIVESTOCK PRODUCTION TECHNOLOGIES - A. Saghir; K. M. Chaudhary; S. Muhammad; A. A. Maan (Journal of Animal and Plant Sciences, 2013)
Pakistan, an agriculture based country, facing gender biasness in farming community. Female farmers are facing an information gap in livestock production sector. For this purpose Okara district (Punjab province) was selected which consists of three tehsils i.e. Okara consists of 30 Rural Union Councils (RUCs), Depalpur (43 RUCs), and Renalakhurd (16 RUCs) which comprise 89 rural union councils. A sample of 30% rural union councils from each tehsil was drawn at random. Two villages from each union council were selected randomly. There were 12 respondents from each village which were selected through purposive sampling. The data were collected through pre-tested and validated interview schedules and were analyzed using Statistical Package for Social Sciences (SPSS) to draw conclusions and to suggest measures for improvement. Results showed that most of the female respondents belonged to young aged group and primary pass. In the context of availability of information sources TV stood first then came the mobile phone, telephone and radio, respectively. Really Old ICTs (print media) got very less position as compared to Old ICTs (TV, radio and telephone) with regard to utility of ICTs. However, regarding the future role of various ICTs in livestock production, modern ICTs stood first then came the old and really old ICTs, respectively. It was concluded from the results that due to less education of the respondents really old ICTs (print media) was less both in availability and utility of ICTs. Whereas, modern ICTs has more scope in the future due to escalating role of internet and mobile in livestock production.
Keywords: Role; ICT; gender gap; information; livestock production